Pengaruh Motivasi Intrinsik, Lingkungan Kerja Psikososial, Kepuasan Kerja, Dan Keadilan Distributif Terhadap Kinerja Tugas Pegawai Kesehatan Yogyakarta - Pradana, Hanung Wahyu; Kurniawan, Ignatius Soni; Purnamarini, Tri Ratna (Universitas Islam Kadiri, 2025)
This study aims to analyze the influence of intrinsic motivation, psychosocial work environment, job satisfaction, and distributive justice on employee task performance in healthcare institutions. The originality of this research lies in its comprehensive exploration of these variables within the context of healthcare institutions in Yogyakarta, addressing unresolved issues in previous studies. This research employs a quantitative approach with data collected from 100 respondents using a Likert scale questionnaire (1-5). The data were analyzed using statistical methods, including validity tests, reliability tests, classical assumption tests, and multiple linear regression to evaluate the relationships between variables. The results indicate that intrinsic motivation has a significant negative effect on task performance, while the psychosocial work environment and job satisfaction have significant positive effects. Meanwhile, distributive justice does not show a significant effect on task performance. The implications of this research highlight the importance for organizations to create a conducive psychosocial work environment and enhance job satisfaction. This study also provides a foundation for further research to explore other relevant variables in the context of performance management in healthcare institutions.